The Effect of Weight Training Using Tools on Chest Pass Ability - Yolly Devira; witarsyah - (Performa, 2019)
The problem in this research is the lack of ability of the athlete basketball chest pass Batavia club Padang. The purpose of this study to determine the effect of weight training is there to use the tool in the ability of the athlete basketball chest pass Batavia club Padang. This study is a quasi-experimental research. The research was conducted on July 4 until August 7th, 2019 in Padang Development high school basketball court. The population in this study as many as 22 people consisting of 10 sons and 12 daughters. The sample in this study is the son of basketball athletes sma level of development of Padang about 10 people. The study was conducted as many as 16 times in one week a meeting where there are four times the exercise. Instruments in this study using Wallbounce Basketball Passing Test. Data analysis techniques in this study using the formula t test. From the research and hypothesis testing can be concluded that there is a significant effect of strength training using a tool on the ability of the athlete basketball chest pass Batavia club Padang.